2016
DOI: 10.1111/rda.12678
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Neospora Caninum Infection in Pregnant Dairy Heifers Raises Concentrations of Pregnancy‐Associated Glycoproteins 1 and 2 in Foetal Fluids

Abstract: Plasma concentrations of PAG-1 are used for pregnancy diagnosis and as a marker of placental/foetal well-being, while those of PAG-2 may be an indicator of abortion risk in Neospora caninum-infected cows. Studies have shown that N. caninum infection modifies PAG-1 and PAG-2 patterns in maternal blood plasma. However, no prior work has examined the effects of N. caninum infection on concentrations of PAGs in foetal fluids. In this study, PAG-1, PAG-2 and pH levels were determined in the amniotic and allantoic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Despite the fact that there have been various works on bovine animals [ 120 , 121 , 122 , 123 ] in which PAGs were measured using also antibodies raised against PAG-2, to our knowledge, only two works exist in which this method was reported for buffalo species [ 124 , 125 ]. The results of these works showed that the threshold value of 1.0 ng/mL was not reached before day 40 post-AI, although significant differences between pregnant and non-pregnant buffaloes were found starting from Day 28 post-AI.…”
Section: Other Livestock Speciesmentioning
confidence: 99%
“…Despite the fact that there have been various works on bovine animals [ 120 , 121 , 122 , 123 ] in which PAGs were measured using also antibodies raised against PAG-2, to our knowledge, only two works exist in which this method was reported for buffalo species [ 124 , 125 ]. The results of these works showed that the threshold value of 1.0 ng/mL was not reached before day 40 post-AI, although significant differences between pregnant and non-pregnant buffaloes were found starting from Day 28 post-AI.…”
Section: Other Livestock Speciesmentioning
confidence: 99%
“…To our knowledge, this is the first work in which the plasma concentration of PAG molecules during the gestation period was measured using antibodies raised against PAG-2 in buffalo, although, there are various works in which this method has been reported for bovine species [31,32,34,35]. Although significant differences were found starting from Day 28 post AI, our results show that the threshold value for pregnancy diagnosis (1.0 ng/mL) was only reached at Day 40 post AI, as previously reported for bovine species in [31,32,34,35]. Therefore, this work confirmed that in buffalo as well, the pre-eminent PAG radioimmunoassay method to diagnose pregnancy utilizes antibodies raised against PAG-1, as reported in our previous work [26,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The bovine PAG-2 radioimmunoassay used has been described recently in [31,34,38]. Briefly, PAG-2 was purified according to the method detailed by Beckers et al [39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se especula que algunas funciones placentarias, en preñeces de razas cruza, se cumplen de manera más eficiente probablemente debido al aumento en la expresión de glicoproteínas asociadas a la preñez (pregnancy associated-glycoproteins, PAG). En hembras que abortaron se detectó una disminución considerable en su expresión (López-Gatius et al, 2007;Mur-Novales et al, 2016;Serrano-Pérez et al, 2014, 2016Wooding et al, 2005).…”
Section: -unclassified